Some of South Sumatran Plants Containing Alkaloids - Eliza Eliza; Dasril Basir (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
A phytochemical survey for alkaloid-containing plants has been conducted in South Sumatra including traditional medicinal plants. During the survey 180 satisfactory herbarium sample were obtained and all of them were tested for alkaloids. The results showed that 33 species gave a positive test for alkaloids, and high alkaloid contents were shown by: Alstonia scholaris, Alstonia angustiloba, Ervatamia coronariaa, Voacanga foetida Bl. K. Schum, Litseaacceden toides K & V, Litsea angualata, Litsea tomentosa, Fibraurea chloroleuca Miers (root), and Uncaria cordata (Lour.) Merr. The aboved survey was also continued to be an intensively phytochemical work focusing on alkaloid of Fibraurea chloroleuca Miers root.  A quaternary isoquinoline alkaloid as a yellowish crystal, m.p. 214-215 oC; MS (FAB) m/z 352 has been successfully isolated and tested for antibacterial activity.  This isolated alkaloid significantly inhibited Bacilus substilis, Shigela dysentriae, Staphylococus aireus, and Pseudomonas sp growth at 1 mg/mL. As a result, all of these alkaloid-containing plants are potential to explore their alkaloids and utilitarian for traditional medicines.Keywords: Alkaloids, traditional, medicines, south sumatra, plants